Magnetic purification of antibodies - Dhadge, Vijaykumar Laxman (2016)
This work aimed at the development of magnetic nanoparticles for antibody purification and at the evaluation of their performance in Magnetic fishing and in a newly developed hybrid technology Magnetic Aqueous Two Phase Systems. Magnetic materials were produced by coprecipitation and solvothermal approaches. Natural polymers such as dextran, extracellular polysaccharide and gum Arabic were employed for coating of iron oxide magnetic supports. Polymer coated magnetic supports were then modified with synthetic antibody specific ligands,namely boronic acid, a triazine ligand (named 22/8) and an Ugi ligand (named A2C7I1). To optimize the efficacy of magnetic nanoparticles for antibody magnetic fishing, various solutions of pure and crude antibody solutions along with BSA as a non-specific binding protein were tested. The selectivity of magnetic nanoparticle for antibody, IgG, was found effective with boronic acid and ligand 22/8. Magnetic supports were then studied for their performance in high gradient magnetic separator for effective separation capability as well as higher volume handling capability. The magnetic materials were also supplemented to aqueous two phase systems, devising a new purification technology. For this purpose, magnetic particles modified with boronic acid were more effective. This alternative strategy reduced the time of operation,maximized separation capability (yield and purity), while reducing the amount of salt required. Boronic acid coated magnetic particles bound 170 ± 10 mg hIgG/g MP and eluted 160 ± 5 mg hIgG/g MP, while binding only 15 ± 5 mg BSA/g MP. The affinity constant for the interaction between hIgG and APBA_MP was estimated as 4.9 × 105 M-1 (Ka) with a theoretical maximum capacity of 492 mg hIgG adsorbed/g MP (Qmax). APBA_MPs were also tested for antibody purification directly from CHO cell supernatants. The particles were able to bind 98% of IgG loaded and to recover 95% of pure IgG (purity greater than 98%) at extremely mild conditions.